Geniscenesættelse - en selvskadende traumeefterreaktion - Thimmer, Line Sangild; Hagelquist, Janne Østergaard (Psyke & Logos, 2016)
Re-enactment is unbidden memories of one or more traumatic experiences that return in either physical sensation, reliving or behavioral reconstruction of the trauma (van der Kolk, 1989). It is a recurrent self-harming trauma reaction, where the traumatized person is locked in a position of repeating elements of the original trauma, which expresses a fundamental wish for learning and healing. Re-enactment is related to difficulties mentalizing because the traumatized person has problems thinking about or emotionally relating to the trauma. This article will try to describe the function of self-harm in the sense of re-enactment amongst developmentally traumatized persons. The article finds that reenactment is an expression of the developmentally traumatized persons repeated thoughts and stress related to the trauma. The motives are therefore a wish to find peace for the difficult emotions related to the trauma, bad trauma habits and a fundamental wish for a more coherent self and better relations. When traumatized people re-enact it creates tremendous frustration amongst the professionals surrounding them. Ultimately in the article we suggest how you may help traumatized persons break the vicious cycle of re-enactment.